Piezosurgery for Excision of Large Osteoid Osteoma. Issue 7 (October 2016) - Gadre, Pushkar; Singh, Divya; Gadre, Kiran; Khan, Imran
Abstract : Abstract: Osteoid osteoma, a rare benign osteoblastic tumor first described by Jaffe in 1935, is characterized as a small but painful lesion that mostly affects younger people. Usually benign and harmless, osteomas are removed for pain or esthetic reasons. Piezoelectric surgery is also increasingly being used effectively in major and minor osseous oral and maxillofacial surgeries, in delicate areas. It is used regularly for various procedures, including sinus lift procedures, bone graft harvesting, osteogenic distraction, ridge expansion, inferior alveolar nerve decompression and lateralization, cyst removal, dental extraction, and impacted tooth removal. The following report presents a patient of intraoral excision of a large osteoid osteoma from lingual aspect of mandibular lower border in the body region using piezoelectric surgery.